Anal reconstruction after a rare complication of routine haemorrhoid treatment. Issue 4 (November 2016) - Yeung, Carol Kwan‐Lok; Choi, Chi‐Yee; Chow, Tam‐Lin
Abstract : Anal stenosis is a well‐documented complication that can occur from anorectal surgery. This condition can be disabling and causes significant patient discomfort. Various surgical techniques for the treatment of anal stenosis have been described in the literature, however, its successful management still remains as a technical challenge. Here, we present a case of a patient who suffered from anal stenosis after a complication of sclerotherapy treatment of haemorrhoid, which was successfully managed by anal reconstruction with V‐Y advancement flaps.